Mutu Organoleptik Ikan Julung-julung Asap pada Konsentrasi Asap Cair Berbeda - Zees, Fauzia; Sulistijowati, Rieny; Yusuf, Nikmawatisusanti (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2024)
This research aims to determine the effect of different concentrations of liquid smoke solution on the organoleptic quality of smoked julung-julung fish (Hemirhamphus affinis). The treatment factors are 1% liquid smoke solution concentration (A), 3% liquid smoke solution concentration (B) and 5% liquid smoke solution concentration (C). The organoleptic data analysis used was Kruskall-wallis with test parameters namely appearance, smell, taste, texture. Further test using Duncan. The results of the research showed that all treatments with different concentrations of liquid smoke solution (A, B, C) had no effect on the appearance of the product specifications, namely intact, clean, slightly brown in color and shiny, specific to the type of smoked fish; specifications: less fragrant odor, sufficient smoke and no additional disturbing odors; taste specifications, namely delicious, less savory, and texture specifications, namely dense, compact, quite dry, and tightly intertwined.